2006
DOI: 10.1111/j.1742-7924.2006.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an exercise program for fall prevention for elderly persons in a long‐term care facility

Abstract: Aim:The purpose of this study was to develop an exercise program for elderly individuals in a long-term care facility. Developed through the synthesis of evidence-based nursing with the use of available research related to falls and exercise, the program was designed to increase balance, mobility, and muscle strength in the lower extremities in order to prevent falls and improve the self-efficacy of the patients. Methods: We developed an exercise program consisting of a warm-up, static stretching, muscle stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…We compared our review results with the Cochrane Review ' Interventions for preventing falls in older people living in the community ' (Gillespie 2012), and identified six other systematic reviews incorporating meta-analyses (Chan 2015; Le Blanc 2015; Sherrington 2017; Silva 2013; Stubbs 2015; Vlaeyen 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared our review results with the Cochrane Review ' Interventions for preventing falls in older people living in the community ' (Gillespie 2012), and identified six other systematic reviews incorporating meta-analyses (Chan 2015; Le Blanc 2015; Sherrington 2017; Silva 2013; Stubbs 2015; Vlaeyen 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Sherrington 2017 conducted a systematic review and meta-analysis of exercise interventions to prevent falls in older adults. This review included 14 RCTs (15 comparisons) of exercise interventions in care settings and found no significant effect on the rate of falls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] For example, exercises that target ankle and hip strength have been shown to lower the risk of falling as measured by the incidence of falls among participants three months post-intervention as determined by functional independence measure scores, and the Fall Efficacy Scale. [24] Deley and colleagues [25] investigated the effects of a one-year aerobic endurance and resistance training program on 40 healthy adults over 70 years of age. The use of a combined training program which included three hours a week of exercise included 24 participants and a control group of 16 participants who did not receive the training program.…”
Section: Physiological Factors In Sarcopeniamentioning
confidence: 99%
“…Recent studies have shown the benefits of exercise and physical activity for shortness of breath and continence 16,17 as well as for fall prevention. 18 Formal recommendations by the American College of Sports Medicine (ACSM) and the American Heart Association (AHA) have existed since 1995 and have been updated in recent years, 7,19 but these primarily address exercise prescription for community-dwelling older adults.…”
mentioning
confidence: 99%